2019
DOI: 10.1177/1932296819839099
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Content Analysis of Public Diabetes Facebook Groups

Abstract: Introduction: Relatively little is known about how Facebook groups are used to facilitate diabetes self-management support. This study provides a critical analysis of public diabetes Facebook groups and their content. Methods: Two trained researchers independently identified 34 public Facebook diabetes groups. A coding and classification scheme was applied to the 20 most recent “wall posts” within 15 of the 34 (44.1%) largest groups (n = 300 posts). Nonparametric Mann-Whiney U tests examined differences in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 36 publications
3
47
0
8
Order By: Relevance
“…Being both ubiquitous and freely accessible, social media channels allow patient associations to share content and connect with individuals interested in their health condition. Representing one of the most prevalent chronic diseases worldwide, diabetes associations and diabetes patient groups can also be found on social media [ 1 - 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being both ubiquitous and freely accessible, social media channels allow patient associations to share content and connect with individuals interested in their health condition. Representing one of the most prevalent chronic diseases worldwide, diabetes associations and diabetes patient groups can also be found on social media [ 1 - 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [ 20 ], we surveyed followers of the Norwegian Diabetes Association’s social media channels, and we found that almost all the respondents wanted more content about research and innovation on diabetes in social media groups, preferably in text format. However, other previous studies have reported that social media groups for patients with diabetes mostly shared content about diabetes self-management [ 1 - 4 ], scientific content [ 3 , 4 ], health care services [ 3 , 4 ], diabetes awareness [ 3 , 4 ], personal stories [ 2 ], or humor [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…YouTube is a public platform and people from wide ranging disciplines and contexts access it for information on broad range of topics and issues. As a continually developing online resource for health information, communication, and promotion, health education researchers have examined the use and effectiveness of specific popular social media sites such as YouTube [15,16,17,18], Pinterest [19,20], Instagram [21], and Facebook [22]. Given the popularity, reach, accessibility and unregulated governance of social media, it is critical that users seek and post/upload information from reputable, qualified and trusted health and medical sources.…”
Section: Introductionmentioning
confidence: 99%
“…A purposive sampling method was utilised to include the most reached Facebook pages in each Pacific country so that the data collected would be closely reflective of mainstream regional online public sentiment at the time of analysis. This purposive approach to sampling Facebook groups was inspired by a recent Facebook content analysis project by Stellefson et al [2019] on how Facebook conversations facilitate diabetes self-management support and communication around the medical science of diabetes. The authors selected the 50 largest public diabetes-related Facebook groups based on overall number of members, reach and engagement, with the aim of capturing a strong representative sample of how diabetes is communicated on social media.…”
Section: Methodsmentioning
confidence: 99%